STORYBOARDING AS A PEDAGOGICAL TOOL: FOSTERING LANGUAGE, LITERACY, AND CREATIVITY THROUGH VISUAL NARRATIVES - S. Sangeetha (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Visual storytelling is a powerful tool in literature for fostering emotional influences with students. Innovative methods like visual storytelling transform English language teaching into more engaging and effective. Multimedia learning has become crucial for learning, engaging, and motivating learners with Education 4.0. This study explores the use of storyboarding as a pedagogical tool in English language teaching. By integrating visual narratives, storyboarding enhances students' understanding of literature, fosters creativity, and promotes literacy. The research demonstrates how visual storytelling can engage students, improve comprehension, and develop critical thinking skills. Through qualitative methods, 10 Postgraduate ESL learners were taken for the case study, and semi-structured interviews were conducted, the study highlights the benefits of combining literature and art in the classroom where they study film and media studies in their course, ultimately contributing to a more dynamic and effective learning experience. Results indicate that visual storytelling using storyboards improves communication skills, motivation, and engagement and enhances students' learning experiences, making learning more interactive and enjoyable.